Pengaruh Kompensasi Terhadap Kinerja Pegawai Di Kantor Kecamatan Caringin Kabupaten Garut - Iis Iskandar Joesoef (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2019)
Abstract : The factors of decreasing the performance of employees in Caringin District Office Garut Regency is the impact of the inappropriate compensation given to the employees. With the compensation can increase the effectiveness of work to achieve corporate organizational goals. Compensation is one of the operational functions in human resources, which regulates the wage / salary and services provided by the company to its employees in return for what has been given to the employee. The method used in this research is by using descriptive research method with quantitative approach. Based on the results of research results of the test using SPSS Version 23 all variables used are declared valid, regression test results generated through SPSS processing is equal to 0.939 or 93.9%. This means that the degree of attachment between independent and dependent variables is 93.9% with the scale of measurement of 100% attachment then in this case 6.10% Compensation in Caringin District Office of Garut Regency influenced by other variables not discussed in this study. In the table is influenced by other variables that are not discussed in this study. In the ANOVA table we can see that the value of the coefficient of degree of deviation is 1. There is a positive and significant relationship between the independent variable and the dependent variable.